2022
DOI: 10.1007/s00018-021-04112-1
|View full text |Cite
|
Sign up to set email alerts
|

Ins and outs of AlphaFold2 transmembrane protein structure predictions

Abstract: Transmembrane (TM) proteins are major drug targets, but their structure determination, a prerequisite for rational drug design, remains challenging. Recently, the DeepMind’s AlphaFold2 machine learning method greatly expanded the structural coverage of sequences with high accuracy. Since the employed algorithm did not take specific properties of TM proteins into account, the reliability of the generated TM structures should be assessed. Therefore, we quantitatively investigated the quality of structures at gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(100 citation statements)
references
References 73 publications
4
95
1
Order By: Relevance
“…It could be used to predict the protein structure at the atomic level with high accuracy. Besides, the protein–protein interactions could be also predicted by AlphaFold2 ( Tunyasuvunakool et al, 2021 ; Hegeds et al, 2022 ). In this study, three SEP proteins, DEFICIENS-like protein (AKC93996.1) and flower meristem identity protein LEAFY (AKC94104.1) in P. henryanum were selected for the prediction of the protein–protein interactions ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…It could be used to predict the protein structure at the atomic level with high accuracy. Besides, the protein–protein interactions could be also predicted by AlphaFold2 ( Tunyasuvunakool et al, 2021 ; Hegeds et al, 2022 ). In this study, three SEP proteins, DEFICIENS-like protein (AKC93996.1) and flower meristem identity protein LEAFY (AKC94104.1) in P. henryanum were selected for the prediction of the protein–protein interactions ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The AlphaFold structural database currently has nearly a million protein structures available, including complete proteomes for Homo sapiens and 47 other species ( Jumper et al, 2021 ; Tunyasuvunakool et al, 2021 ). These structures are rapidly facilitating an unprecedented understanding of structural biology ( Hegedus et al, 2022 ; Porta-Pardo et al, 2022 ; Varadi et al, 2022 ; Wehrspan et al, 2022 ). Yet, the accuracy of AlphaFold in terms of predicting otherwise unsolved structures is relatively untested since it only became publicly available less than a year ago.…”
Section: A Case For Differential Regulation By the C-terminal Extensionsmentioning
confidence: 99%
“…Moreover, in a recent elucidation of a novel membrane protein called ChRmine, some structural features were reported to be mispredicted by AlphaFold 2 ( Kishi et al, 2022 ). However, in a thorough retrospective study ( Hegedűs et al, 2022 ), which used new membrane protein structures reported after the optimization and launch of AlphaFold 2, the program was found to be likely to perform as well with membrane proteins as with water soluble proteins. For both classes of proteins, disordered regions are modeled with low confidence and for the former they are sometimes incorrectly threaded through the membrane.…”
Section: Introductionmentioning
confidence: 99%